Actitudes hacia la estadística en universitarios peruano de mediana edad - Tarazona Vargas, Enver (2014)
This paper studies the attitudes of college students concerning statistics; students who are taking the basic course in Statistics under an Adult Worker Student program at a private university in Lima, Peru. Two scales have been considered: Attitudes Toward Statistics (ATSE) proposed by Estrada (2002) and Attitudes Toward Statistics (ATSC) proposed by Cazorla et al (1999). The sample corresponds to 137 students with ages ranging from 32 to 42 years old, from four engineering majors, , 84% male and 52% who had taken a previous course in statistics. The item analysis was performed considering the Classical Test Theory (CTT) and Item Response Theory (IRT) under the Bayesian inference of the Samejima’s graded response model (Tarazona, 2013). The results reveal that AEC has a reliability of 0.93, and by comparison a shortened version of AEE after eliminating two items has a reliability of 0.88. Both scales are closely correlated are therefore are interchangeable. However AEE is the only one that reveals differences by specialty, especially among students of the School of Industrial Engineering (positive attitudes), and of Telecommunications and Network Engineering (less positive attitudes). Finally, other factors such as gender, different age groups and experience in a previous course of Statistics were insignificant in explaining attitudes toward statistics at any scale.